Interfacial Magnetic Features of La2CoMnO6/Pt Bilayers Studied by Using Spin Hall Magnetoresistance. Issue 31 (25th September 2022) - Martín‐Rio, Sergi; Frontera, Carlos; Gómez‐Pérez, Juan M.; Aguilar‐Pujol, Montserrat X.; Catalano, Sara; Gázquez, Jaume; Casanova, Fèlix; Balcells, Lluis; Pomar, Alberto; Martinez, Benjamin
Abstract: Spin Hall magnetoresistance (SMR) is used to study interfacial magnetic features in La2 CoMnO6 (LCMO)/Pt bilayers. LCMO is a ferromagnetic insulator with a Curie temperature T c = 250 K and a strong magnetic anisotropy that can be tuned by microstructural strain. However, SMR measurements do not show any dependence on the strained state of the LCMO films. In addition, contrary to what may be expected, SMR signal persists above T C exhibiting a strong magnetic field dependence well above the saturation of the magnetization while the typical hysteresis on crossing H = 0 is absent. All these results suggest that the uppermost LCMO interfacial layers are magnetically uncoupled from the rest of the LCMO film and they do not show long range magnetic ordering. This fact is confirmed by a complete scanning transmission electron microscopy study of the interface that makes evident that the last atomic layers of the LCMO film do not contain Co and have a LaMnO3+ δ simple perovskite‐like structure with the last atomic layer being lanthanum oxide. The analysis of the experimental results according to recent SMR theories indicates, in fact, that the LCMO interfacial layer behaves as a 2D Heisenberg ferromagnet. Abstract : Interfacial magnetic features of La2 CoMnO6 (LCMO)/Pt bilayers are studied by using Spin Hall magnetoresistance (SMR). Magnetoresistance signal persists well above the Curie temperature, TC, exhibiting strong magnetic field dependence while the typical hysteresis on crossing field H = 0 is absent. These results suggest that the uppermost LCMO interfacial layers are magnetically decupled from the rest of the LCMO film.